Development of copper coating technology on high strength low alloy steel filler wire for aerospace applications. (2018) - Ramkumar, P.; Gino Prakash, F.; Karthikeyan, M.K.; Gupta, R.K.; Muthupandi, V.
Abstract: 0.3C-CrMoV(ESR) grade steel is considered as a potential candidate for realizing solid booster cases in aerospace applications due to its high strength coupled with toughness. To obtain the maximum weld efficiency, these steels are welded using filler wires of the same chemical composition. However, due to inherent corrosive nature, bare filler wires could not be stored for long time. To overcome this problem, a suitable coating technology using copper as coating material has been developed which provides uniform, adherent and thin coating on the wire and do not impair the required mechanical properties of weldment. In order to alleviate the gas pick-up issues associated with electro-plating technique and considering the product configuration, immersion coating technique was adopted. Process optimization to obtain a uniform and adherent coating on wire spools was carried out. Wires were also analysed for coating thickness, adhesion and gases (O, H, N). Coating has been observed to be adherent and gas content were found within the aerospace specification. Further, weldment realized using coated filler wire shows similar quality of weldments and properties as obtained through uncoated filler wire, confirming this process and coating can be adaptable for storage of filler wire.